Transformation of the immobile part of the light petroleum products in the geological environment - Брикс, А. Л.; Негода, Ю. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The article is devoted to principles of hydrocarbon pollution cluster formation in geological environments, the part of the contaminant accumulation that consists of immobile oil products, not the lenses of the light oil products. This fluid is retained by soils in aeration and saturated zones, and for many years it has been the source of hydrocarbons that pollutes the aquifer.The important reason for investigation is the periodic transition of oil products from the mobile to the immobile state and vice versa, depending on the direction of the oscillatory movement of the groundwater levels.The purpose of the article. Research of the state of the petroleum product pollutant is necessary for the differentiated determination of quantitative indicators and assessment of the threat posed by the individual components of the contamination foci.Methods. The authors’ own achievements, as well as the research results of native and foreign investigators made the methodical basis for the article.Results. As an example of the need to study the oil product clusters in the geological environment in depth, the results of studies conducted on the territory of the airfield near the city of Mykolaiv (Ukraine) are presented. A layer of mobile kerosene, located on the surface of a perched aquifer was discovered here.Scientific novelty and practical significance. A feature of oil pollution formation on a special type of aquifer, the so-called perched aquifer is considered.Additional attention should be paid to identification and evaluation of oil product liquids blocked in the water saturated zone.Keywords: geological environment, light oil products, immobile oil liquid, perched aquifer, transformation of contaminant cluster.